2022
DOI: 10.1186/s12877-022-03454-0
|View full text |Cite
|
Sign up to set email alerts
|

Potential association between frailty and pTau in community-dwelling older adults

Abstract: Background Frailty is a geriatric syndrome characterized by a decline in physiological reserves, and multiple factors contribute to the occurrence and development of frailty. Growing evidence supports a strong link and overlap between frailty and cognitive impairment, but the mechanisms involved have not yet been fully elucidated. Aim To identify associations between 12 plasma cognition-related biomarkers and frailty in community-dwelling older adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
2
0
1
Order By: Relevance
“…Fourth, we found an association between frailty and several proteins associated with neurodegenerative processes. Indeed, several proteins related to AD were associated with FI, more particularly in amyloid metabolism (Lu et al., 2021; Zhou et al., 2022). We found a negative association between FI and APP, the precursor of β‐amyloid, and its homolog, APLP2, as well as SORL1, a regulator of endosomal recycling of APP (Mishra et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, we found an association between frailty and several proteins associated with neurodegenerative processes. Indeed, several proteins related to AD were associated with FI, more particularly in amyloid metabolism (Lu et al., 2021; Zhou et al., 2022). We found a negative association between FI and APP, the precursor of β‐amyloid, and its homolog, APLP2, as well as SORL1, a regulator of endosomal recycling of APP (Mishra et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that frailty exacerbates the release of these vesicles in patients with MCI. Zhou et al, (2022) examined a range of neural biomarkers that have been associated with cognitive decline and dementia in relation to any link to frailty (tTau, pTau (Thr181), NFL, Aβ40, Aβ42, S100B 1, VLP-1, AD7cNTP, βAPP, CHI3L1, sCR1 and hFABP). pTau was related to frailty, but other plasma biomarkers were not, including beta amyloid, a marker for Alzheimer's Disease (AD).…”
Section: Cf and Clinical Markers Of Inflammationmentioning
confidence: 99%
“…Los adultos mayores de 65 años son más vulnerables debido a los cambios fisiológicos asociados con la edad, además de la presencia de comorbilidades y polifarmacia, siendo esta última considerada como la formulación de 5 o más medicamentos. 2 En el adulto mayor la motilidad intestinal y el flujo sanguíneo regional son menores, hay disminución en el metabolismo del primer paso, pérdida del volumen hepático de 20 a 40% 3 , cambios en los compartimentos corporales, aumento en la grasa corporal, pérdida de un tercio en el peso renal, alteraciones en la eliminación de los productos xenobióticos 3 y cambios en la dinámica de los medicamentos que obligan a considerar ajustes en las dosis y forma de administración.…”
unclassified